O museu como espaço midiático: da exposição ao entretenimento - Ferrara, Fabiano D Alessio (2013)
The object of the present research is the museum in the transformation processes which mark its cultural function and transcend its character of keeper of memory. The main objective is to study the multiple and paradoxal functions of the museum that range from exhibition to contemplation and entertainment, through images combined, in convergence, with other mediatic codes. Under this light, the basis of this research is the following question: In the present day, how is the cultural function of museums redefined, transforming them in recurring mediatic agents, with multiple actions in the contemporary city? The hypothesis under examination considers the following: 1) the museum as a communication device which constitutes a multimedia space that demands a review of the role of images and visibility in cultural exhibitions and scientific dissemination; 2) under this mulitmediatic paradigm, exhibition projects are contaminated by display models dominated by digital media in order to guarantee the necessary and/or desired interactivity with the public, regardless of the theme of the exhibition; 3) such paradigm makes the social system behave as a medium that models preferences, tastes and social, economic and cultural patterns; 4) the transformation of contemporary museums into communication devices explains and justifies their constant insertion in the cultural redefinition of urban spaces. The corpus of the present research encompasses national museums located in the city of São Paulo (Museu da Língua Portuguesa, Masp, Catavento, Pinacoteca, Do Futebol) as well as notable international examples such as, the Louvre, Gare D´Orsay, Quai Branly, Pompidou, and Guggenheim/Bilbao. The research methodology consists in the discrimination of visuality characteristics of museums, comparison among the several manifestations, observation of their respective contexts or themes, as well as an attempt to define the cultural roles such museums play in the cities where they are located. In order to do this, the research relies on fundamental concepts such as: iconofagia , technical reproducibility of the images, image cult, zero-dimensionality of the image, social taste, codification of look and space, developed by scholars in the field of semiotics of culture, image, and media, such as Norval Baitello Jr., Walter Benjamim, Vilém Flusser, Hans Belting, Didi Hubermann, Jacques Rancière, Pierre Bourdieu and Lucrécia Ferrara